Can Utilities Realize the Benefits of Advanced Metering Infrastructure? : Lessons from the World Bank’s Portfolio - Nangia, Varun; Oguah, Samuel; Gaba, Kwawu (World Bank, Washington, DC, 2016)
Advanced metering infrastructure (AMI) provides significant benefits to utilities around the world. Although it is entering the mainstream, technical concerns, policy challenges, capacity, and will in the Bank’s client countries hinder wider adoption. Starting out with smaller AMI deployments aimed at addressing revenue constraints seems to offer the best chance of success at utilities supported by Bank financed projects.